Salvia leucantha essential oil encapsulated in chitosan nanoparticles with toxicity and feeding physiology of cotton bollworm Helicoverpa armigera - Dinesh, Devakumar; Murugan, Kadarkarai; Subramaniam, Jayapal; Paulpandi, Manickam; Chandramohan, Balamurugan; Pavithra, Krishnasamy; Anitha, Jaganathan; Vasanthakumaran, Murugan; Fraceto, Leonardo Fernandes [UNESP]; Wang, Lan; Shoiu-Hwang, Jiang; Dahms, Hans-Uwe (Elsevier, 2021)
We investigated the effect of encapsulated Chitosan-nanoparticles by using Salvia leucantha essential oil on the insecticidal activity against H. armigera, S. litura and P. xylostella. The encapsulated nanoparticles were characterized by UV-vis, SEM, EDX, FTIR and ZP. Phytochemical analysis of essential oil revealed that the presence of alkaloid, flavonoids, phenolics, and glycosides etc., and GC/MS analysis identified at least 12 compounds, the most abundant constituents were bornyl acetate, 1-Octadecanesulphonyl Chloride, spathulenol and caryophyllene oxide. Bioassays was conducted to find out the toxicity against H. armigera and LC50 values of essential oil was 175.39ppm (larva I) 542.09ppm (pupa), and encapsulations of essential oil was 14.56ppm (I) 63.28ppm (pupa), respectively. Life history parameters and food efficiency utilization measures were significantly affected with concomitant decline in the activities of digestive enzymes after treatment of encapsulated Chitosan-nanoparticles for H. armigera, S. litura and P. xylostella. From the results the nanomatierals are effective and eco-friendly bio-insecticides for not only control bollworm and also other lepidopteran insects such as Spodoptera litura and Plutella xylostella at different crop ecosystem.
Keywords: Biopesticides; Chitosan; Encapsulation; Essential oil; Lepidopteran insects; Nano-characterization; Volatile compounds